Beyond succession planning : new ways to develop talent - Spina, Lori; Spina, James D. (Emerald Publishing Limited, 2021)
We hear a lot about the necessity of meeting needs of changing markets by developing people, but we hear less about ways implement change. How can we design effective ways to implement change and maintain and build job satisfaction? James and Lori Spina illustrate how a strategic system aligns workplace transitions with the organizational vision, mission, and top level strategies to meet the needs of all stakeholders, ensure a steady flow of talent from within, and anticipate abilities and skills for jobs not yet created. They provide a road map for how to carry this out and propose a cutting-edge leadership style to complement this strategic approach and beat the competition. They demonstrate in detail on how to meet the emerging learning needs of high potential people who are striving to obtain new levels of responsibility. This book is crucial reading for executives who make strategic business decisions to ensure the sustainability and growth of their organizations.